Drill and broadcast establishment methods influence interseeded cover crop performance in organic corn. Issue 1 (31st January 2020) - Wallace, John M.; Isbell, Sarah; Hoover, Ron; Barbercheck, Mary; Kaye, Jason; Curran, William S.
Abstract: Organic grain producers are interested in interseeding cover crops into corn ( Zea mays L.) in regions that have a narrow growing season window for post-harvest establishment of cover crops. A field experiment was replicated across 2 years on three commercial organic farms in Pennsylvania to compare the effects of drill- and broadcast-interseeding to standard grower practices, which included post-harvest seeding cereal rye ( Secale cereale L.) at the more southern location and winter fallow at the more northern locations. Drill- and broadcast-interseeding treatments occurred just after last cultivation and used a cover crop mixture of annual ryegrass [ Lolium perenne L. ssp. multiflorum (Lam.) Husnot] + orchardgrass ( Dactylis glomerata L.) + forage radish ( Raphanus sativus L. ssp. longipinnatus ). Higher mean fall cover crop biomass and forage radish abundance (% of total) was observed in drill-interseeding treatments compared with broadcast-interseeding. However, corn grain yield and weed suppression and N retention in late-fall and spring were similar among interseeding treatments, which suggests that broadcast-interseeding at last cultivation has the potential to produce similar production and conservation benefits at lower labor and equipment costs in organic systems. Post-harvest seeding cereal rye resulted in greater spring biomass production and N retention compared with interseeded cover crops at the southern location, whereas variable interseeding establishment success and dominance of winter-killed forage radish produced conditions that increased the likelihood of N loss at more northern locations. Additional research is needed to contrast conservation benefits and management tradeoffs between interseeding and post-harvest establishment methods.